LA W OF TRADE MARKS IN INDIA - WITH INTRODUCTION TO INTELLECTUAL PROPERTY. .: By Ashwani Kumar Bansal. CLIPTRADE (Centre for Law, Intellectual Property and Trade), Delhi, 2006 (NATIONAL CAPITAL LAW JOURNAL, 2006)
NA
Keywords: Intellectual Property Rights; Trade Marks; Trade Marks Act 1999; WTO-TRIPS; Brand Protection; Infringement And Passing Off; Domain Names; International Registration Of Mark; Licensing Of Trade Marks; Industrial Property Protection.